2018
DOI: 10.17826/cumj.340629
|View full text |Cite
|
Sign up to set email alerts
|

Üniversitede okuyan kız öğrencilerde depresyon prevalansı ve ilişkili faktörler

Abstract: AbstractÖz Purpose: This study was performed to determine the prevalence of depression and to investigate the correlation between sociodemographic, individual and health-related factors and depression. Materials and Methods: This cross-sectional study was carried out on 618 university students. Participants of the study were first year female students of Vocational School of Health Services, School of Physical Therapy and Rehabilitation, Faculty of Nursing, Faculty of Medicine in the health campus of Dokuz Eyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…A review of the national literature revealed no recent study on mental health representing the society as a whole for a considerably long period. Especially since 2000s, studies on depression involving different groups such as women, adolescents, and students who are more sensitive and vulnerable than other groups in the society have been carried out [2,11,12]. However, a large-scale study representing the whole society has not been conducted, and the factors affecting depression have not been examined.…”
mentioning
confidence: 99%
“…A review of the national literature revealed no recent study on mental health representing the society as a whole for a considerably long period. Especially since 2000s, studies on depression involving different groups such as women, adolescents, and students who are more sensitive and vulnerable than other groups in the society have been carried out [2,11,12]. However, a large-scale study representing the whole society has not been conducted, and the factors affecting depression have not been examined.…”
mentioning
confidence: 99%